ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN RENDAHNYA BED OCCUPANCY RATE (BOR) DI RUMAH SAKIT UMUM NATAMA TEBING TINGGI - Ariska, Dini; Sitio, Sri Sudewi Pratiwi; -, Efrata Sembiring (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2024)
The Bed Occupancy Rate (BOR) quantifies the amount of time that beds are either fully or partially occupied within a certain time period. When the BOR is low, it means that hospital facilities are underutilized. This study employs a cross-sectional methodology and is quantitative in nature. Executed between February and May of 2024 in the Natama Tebing Tinggi General Hospital. After averaging 87 patients each month over the course of a year, this study's population consisted entirely of inpatients at Natama Tebing Tinggi Hospital. In this study, the total population is used as the sample. The study's findings confirm that Natama General Hospital's bed utilization is still subpar and unsatisfactory. The bivariate test found that distance, health workers' attitudes, service facilities' availability, and service quality were all significantly related to the low bed occupancy rate (BOR) at Natama Tebing Tinggi General Hospital in 2023. The multivariate test confirmed this relationship, and the variable Availability was the only one that showed any significant relationship. Among the many factors influencing the 2023 Natama Tebing Tinggi General Hospital's Low Bed Occupancy Rate (BOR), the one most strongly correlated with Service Facilities was the Preval__ence Ratio of 4,013 (1,176-13,687), which indicates that there is a 4.01-fold relationship between the two variables. In order for the community to receive the best possible services, it is expected that RSU Natama Tebing Tinggi will enhance the quality of service. This can be achieved, for example, by paying closer attention to and improving the maintenance of existing facilities and infrastructure, as well as by providing sufficient facilities and infrastructure. From the comfort of patient care rooms, particularly in third class, to the provision of clean restrooms, parking spots for visitors, and comfortable waiting areas for patients and their families, we aim to enhance the experience of those seeking treatment or visiting.